The Interaction Between Family Functioning and the PCDH9 rs9540720 Polymorphism on Major Depressive Disorder in Chinese Freshmen - Qin Y; Hu S; Niu S; Zhang W; Sun H; Xu R; Li H; Mu F; Liu N; Wang J; Sun H; Zhang Y; et al. (Psychology Research and Behavior Management)
Yan Qin,1,2,* Shuzhang Hu,1,2,* Sifang Niu,2,3 Weixin Zhang,4 Hao Sun,4 Ruixue Xu,2,3 Hanyun Li,5 Fuqin Mu,6 Ning Liu,7 Jianli Wang,6,8 Haiya Sun,9 Ying Zhang,10 Yan Liu2,8 1School of Public Health, Shandong First Medical University and Shandong Academy of Medical Sciences, Jinan, 250117, People’s Republic of China; 2School of Public Health, Jining Medical University, Jining, 272013, People’s Republic of China; 3School of Public Health, Binzhou Medical University, Yantai, 264003, People’s Republic of China; 4The First Central Clinical School, Tianjin Medical University, Tianjin, 300270, People’s Republic of China; 5Cheeloo College of Medicine, Shandong University, Jinan, 250012, People’s Republic of China; 6School of Mental Health, Jining Medical University, Jining, 272013, People’s Republic of China; 7School of Basic Medicine, Jining Medical University, Jining, 272067, People’s Republic of China; 8Department of Community Health and Epidemiology, Faculty of Medicine, Dalhousie University, Halifax, B2N5E3, Canada; 9School of Nursing, Jining Medical University, Jining, 272067, People’s Republic of China; 10School of Public Health, University of Sydney, Sydney, NSW, 2006, Australia*These authors contributed equally to this workCorrespondence: Yan Liu, School of Public Health, Jining Medical University, Jining, 272013, People’s Republic of China, Email hakunaly@163.comObjective: Unhealthy family functioning and Protocadherin 9 (PCDH9) have been recognized as potential environmental and genetic risk factors for major depressive disorder (MDD). This study examined the effects of the interaction between PCDH9 and family functioning on MDD in first-year university students.Methods: A cohort of 6985 first-year university students in China was established in 2018 and was followed for one year. The blood samples from 4866 of these participants (38.88% males, mean age:18.42) were genotyped. MDD was assessed using the Composite International Diagnostic Interview-3.0 (CIDI-3.0), while family functioning was evaluated with the Family Assessment Device (FAD). Logistic regression was used to examine the interaction of these two risk factors.Results: The one-year prevalence of MDD was 2.4%. Among first-year university students, the AA genotype of rs9540720 (PCDH9) was a protective factor for MDD (OR=0.47, 95% CI: 0.23– 0.88, P=0.025). Affective responsiveness was a risk factor for MDD (OR=1.77, 95% CI: 1.13– 2.78, P=0.013). The interaction between AA genotype of rs9540720 and general functioning was statistically significant for MDD (OR=6.83, 95% CI: 1.16– 39.27, P=0.031), indicating that unhealthy family functioning may exacerbate the risk of MDD in carriers of this genotype.Conclusion: University students carrying the AA genotype of rs9540720(PCDH9) may have a higher probability of developing MDD when they have unhealthy family functioning. The etiological mechanism of depression in university students is explained from the perspective of gene-environment interaction and provides a theoretical basis for subsequent effective identification and screening of high-risk groups for depression in university students.Keywords: depression, family functioning, gene-environment interaction, PCDH9 rs9540720, freshman